1987
DOI: 10.1121/1.395560
|View full text |Cite
|
Sign up to set email alerts
|

Potentials evoked by the sinusoidal modulation of the amplitude or frequency of a tone

Abstract: Steady state responses to the sinusoidal modulation of the amplitude or frequency of a tone were recorded from the human scalp. For both amplitude modulation (AM) and frequency modulation (FM), the responses were most consistent at modulation frequencies between 30 and 50 Hz. However, reliable responses could also be recorded at lower frequencies, particularly at 2-5 Hz for AM and at 3-7 Hz for FM. With increasing modulation depth at 40 Hz, both the AM and FM response increased in amplitude, but the AM respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
143
2
5

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(169 citation statements)
references
References 0 publications
18
143
2
5
Order By: Relevance
“…Direct FM-generated aSSR, i.e., at the frequencies of ƒ FM (2.1-30 Hz), were also observed, in agreement with previous findings (Dimitrijevic et al 2001;Luo et al 2006;Picton et al 1987). For example, the stimulus with ƒ FM of 8 Hz elicited an aSSR response peak at 8 Hz, and the stimulus with ƒ FM of 30 Hz elicited an aSSR response peak at 30 Hz, in addition to any sidebands around the AM generated SSR.…”
Section: Auditory Steady-state Responsesupporting
confidence: 79%
See 1 more Smart Citation
“…Direct FM-generated aSSR, i.e., at the frequencies of ƒ FM (2.1-30 Hz), were also observed, in agreement with previous findings (Dimitrijevic et al 2001;Luo et al 2006;Picton et al 1987). For example, the stimulus with ƒ FM of 8 Hz elicited an aSSR response peak at 8 Hz, and the stimulus with ƒ FM of 30 Hz elicited an aSSR response peak at 30 Hz, in addition to any sidebands around the AM generated SSR.…”
Section: Auditory Steady-state Responsesupporting
confidence: 79%
“…This 40-Hz oscillatory activity has been proposed to result from the resonant properties of the thalamocortical system (Llinas 2000) and interactions between excitatory and inhibitory neurons (Freeman 2000). It has also been suggested that the elicited aSSRs reflect the resetting of this 40-Hz brain rhythm by transients in the sensory input, which could also explain the maximum aSSR for modulation frequency ϳ40 Hz across various stimulus types (Picton et al 1987;Rees et al 1986;Regan 1989;Ross et al 2000;Stapells et al 1984). A study of the aSSR to pure AM sound (Ross et al 2000) systematically examined the effects of stimulus properties (modulation frequency, carrier frequency) on the aSSR (amplitude and phase).…”
Section: Relationship With General Neural Oscillationsmentioning
confidence: 99%
“…The ASSR is an oscillation in auditory cortex evoked by repetitive auditory stimulation at a fixed frequency. The response is most consistent around 40 Hz (Picton et al, 1987), suggesting that the neural network has a resonance at this particular frequency, which is also consistent with other experimental and theoretical data (Wang and Buzs á ki, 1996;Cardin et al, 2009). As discussed above, previous studies suggest that the 40-Hz oscillation is primarily driven by mutually connected inhibitory interneurons.…”
Section: Parallels To Other Conditions Involving Cortical Dysfunctionsupporting
confidence: 80%
“…Similar results were reported for the frequency modulated following response (FMFR), a steady-state evoked response thought to be related to frequency discrimination. Boettcher et al (2002) reported that FMFR response amplitudes increased as a function of modulation depth over depths of 0-40%, then reached a plateau , whereas Picton et al (1987) reported a relatively linear increase in response amplitude for modulation depths of 10-70%, with increases in amplitude tapering off at higher modulation depths . Additionally, increases in response amplitudes and latencies elicited by a change in frequency were comparable to changes in response amplitudes and latencies elicited by increases in intensity, such that responses to small changes in intensity have longer latencies and smaller amplitudes than responses to larger changes in intensity (Harris et al, 2007).…”
Section: Effect Of δF On P1 N1 and P2 Response Latencies And Amplitmentioning
confidence: 99%